Kewenangan Kelurahan Pasca Undang-Undang Nomor 9 Tahun 2015 Tentang Pemerintahan Daerah Kaitannya Dengan Otonomi Daerah - okparizan, okparizan (Jurnal Ilmu Administrasi Negara (JUAN), 2016)
Decentralization can be defined as the delivery of affairs by the central government to the regions based on the principle of autonomy. The Village can be interpreted as a form of "local state government", or the state government at the level of local communities. Urban Village will no longer have full authority and autonomy over the provision of political decision-making in the region. Lurah legal position is under the District government. This is apparent in Act No. 9 of 20015 on Pemerintahn Regions. In this study, the authors conducted a qualitative descriptive analysis, to determine the extent of the authority of the Village in carrying out government activities in the territories kerjannya. The result is clearly illustrated that the village no longer have the authority and the full steering function in terms of coordination, coaching, facilitation, and pengedalian of rowing or organizer functions directly in the region kerjannya an affair. Village authority has been concentrated at the district level. These conditions resulted in village level governance becomes rigid, mechanical and tends to be less dynamic. Decision-making and policy services at village level also diperediksi can not be done quickly, therefore it is more appropriate attributive authority given to the Village to promote the creation of a direct relationship between the general public as the recipient of services, without having to wait for directives or instructions from the District government. In the framework of the implementation of government activities at the village level, the District government should provide "space" which is free to the elements of work equipment in accordance with the administrative duties and functions and regulations that apply so that does not become a barrier for the village in terms of providing services to the community.